Lingual Forms of Latah Speech Spoken by the Caregiver Mother at the Putri Siti Khadijah Orphanage in Rantau Prapat Study: Psycholinguistics - Mutiara Sani; Gustianingsih Gustianingsih; Tasnim Lubis (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to describe the lingual form of talkative speech spoken by caregivers at the Rantau Prapat City Orphanage, and identify the factors that cause the lingual form of talkative speech spoken by the caregivers at the Rantau City Orphanage. This study uses a qualitative approach from data taken from the words of the caretaker of the Putri Siti Khadijah Orphanage in the City of Rantau Prapat. This research was conducted at the location, namely Jl. Supratman No. 36 Rantau Prapat City, West Billa District, Labuhan Batu Regency, North Sumatra Province. The theory used in this research is psycholinguistics, stimulus-response, factors that cause talkativeness. This study uses a qualitative method with data collection used is the proficient method and the listening method with note and record techniques, and interview techniques that do not. The results found in this study were lingual forms of talkative behavior in the form of words and sentences, including: (1) Koprolalia (2) Ekolalia (3) Auto Ekolalia, and (4) Automatic Obidience.In this study, it was also found that the factors that caused the caretaker of the Putri Siti Khadijah Orphanage in Rantau Prapat City to behave in talkative speech. Factors consist of imitation, suggestion, identification, and sympathy.